Integrated Assessment for Introduction to Engineering, Industrial Seminar and Profession and Introduction to Computer Programming Courses - Zakaria, Zaki Yamani; Sadikin, Aziatul Niza; Hasim, Mimi Haryani; Yunos, Nor Alafiza; Rosli, Aishah; Che Man, Siti Hajjar; Hasbullah, Hasrinah; Mohd Yusof, Khairiyah (Universitas Pendidikan Ganesha, 2024)
This study highlights the challenges faced in integrating first-year chemical engineering courses, namely Introduction to Engineering, Industrial and Professional Seminar, and Introduction to Computer Programming. The main challenge lies in effective integrated assessment, especially in ensuring that students understand the interrelationships between the various disciplines and their applications in real-world contexts. The study aims to develop an effective integrated assessment model based on constructive alignment to support student learning in the three courses, with a focus on solving authentic problems related to sustainability. The courses are designed with an integrated assessment approach through project reports, exhibitions, reflection journals, and learning portfolios. Real-world problems relevant to sustainability are used as the main theme, and assessments are conducted both formatively and summatively to measure learning success. This integrated assessment has succeeded in improving students' skills in critical thinking, communication, and technical abilities. Positive feedback from students and expert panels indicates that this assessment model is effective in connecting the various disciplines and preparing students for real-world challenges.